THE RELATIONSHIP OF PATTERN MENSTRUATION WITH ANEMIA INCIDENT TO FEMALE ADOLESCENT - UTAMI, WORO TRI; P, IKA DIAN (Asuhan Kesehatan : Jurnal Ilmiah Ilmu Kebidanan dan Keperawatan, 2015)
ABSTRACTAt the moment menstruation the woman will experience endometrium liberated accompanying blood exit at each month happend after puberty to with menepouse. Accompanying mentioned condition, the woman can suffer anemia when necessity  reed blood cell not fulfilled, purpose this examination to identify relation pattern menstruation with experience anemia at women adolescent in village Brenggolo District Kalitidu Bojonegoro in 2014.            Kind of this examination to analitic Corelasional with approachement cross sectional. Population all of woman adolescent in the 15-20 age not icluding get married in the village Brenggolo, as many as 70 people and the sample as many as 60 people. Sample can be able with manner probability sampling. Collecting data with kuesioner and observesion, after wards in editing, coding, scoring, tabulating and explaining in type list and diagram.            Result can be able point that more than some woman adolescent in village Brenggolo District Kalitidu Bojonegoro, experience anemia that is 32 respondent (88,9%). This matter caused by pattern menstruation not normal.            Be up a gainst set of problems anemia at woman adolescent, hope for healt official to more increase activity healty education especially about anemia with manner give information about important to consume supplement zinc after menstruation, the result woman adolescent know if consume supplement zinc. Keywords : Pattern Menstruation, Female Adolescent, Anemia. Pada saat menstruasi seorang wanita akan mengalami meluruhnya endometrium, disertai keluarnya darah  yang  terjadi setiap bulan setelah pubertas sampai dengan menepous. Dengan kondisi tersebut, seorang wanita dapat  menderita anemia apabila kebutuhan sel darah merah tidak tercukupi. Tujuan penelitian ini untuk mengidentifikasi Hubungan  pola menstruasi dengan kejadian anemia pada remaja putri di Desa Brenggolo, Kecamatan Kalitidu, Kabupaten Bojonegoro Tahun 2014.Jenis penelitian ini analitik korelasional dengan pendekatan cross sectional.  Populasinya semua  remaja  putri usia15-20 tahun yang belum menikah di Desa Brenggolo,sebanyak 70 orang dan sampelnya sebanyak 60 orang. Sampel diambil dengan cara  probability sampling . Pengumpulan data dengan kuesioner dan observasi, kemudian di editing, coding, skoring, tabulating dan dijelaskan dalam bentuk tabel dan diagram.Hasil yang diperoleh menunjukkan bahwa lebih dari sebagian Remaja putri di Desa Brenggolo Kecamatan Kalitidu, Kabupaten Bojonegoro, mengalami anemia yaitu 32 responden (88,9%). Hal ini disebabkan oleh pola menstruasi yang  tidak  normal.Menghadapi permasalahan anemia pada remaja putri, diharapkan Petugas kesehatan agar lebih menggalakkan  kegiatan  pendidikan kesehatan terutama tentang anemia dengan cara memberikan informasi tentang pentingnya mengosumsi suplemen besi/zinc setelah menstruasi, sehingga remaja putri mengetahui manfaatnya jika mengosumsi suplemen besi/zinc. Kata Kunci : Pola Menstruasi,Remaja Putri,Anemia.